Bride island - Enders, Alexandra (New York : Plume, 2007)
Sick after leaving her husband and young daughter behind--hoping to spare them from her drinking, depression, and a legacy of self-destruction--to seek refuge to a coastal town in Maine near Bride Island, her family retreat, Polly Birdswell has put her life back together and hopes to reunite with her child, but family squabbles over Bride Island could threaten everything she loves.
Keywords: Recovering alcoholics -- Fiction; Domestic fiction